Flaky catalyst and preparation method thereof, carbon nanotube array assembly and preparation method thereof, conductive agent, pole piece and battery

By using a sheet-like catalyst with Q element load gradient on the surface of the carrier, the problem of insufficient growth length of the small/single-wall carbon nanotubes is solved, and the efficient growth of the carbon nanotube array assembly is realized and the conductive network is constructed, which improves the battery material performance.

CN119386876AActive Publication Date: 2025-02-07YONGJIANG LAB
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510013593.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-07
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The prior art is difficult to increase the growth length of the small/single-walled carbon nanotubes while ensuring yield, limiting their application in the field of electrochemical energy storage.

Method used

A sheet-like catalyst is used, and the support surface of the catalyst is composed of a central region and an edge region. The loading of Q elements in the central region is greater than that of the edge region, forming a metal particle distribution suitable for the growth of multi-walled and less/single-walled carbon nanotubes. This guides the efficient growth of carbon nanotube arrays.

Benefits of technology

通过该方法获得的碳纳米管阵列组装体具有显著的取向性,长度可达上百微米,不同直径的碳纳米管协同发挥作用,构建性能优异的导电网络,提高了离子电池负极活性材料的导电 Sex and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386876A_ABST
    Figure CN119386876A_ABST
Patent Text Reader

Abstract

The invention provides a sheet-shaped catalyst and a preparation method thereof, a carbon nanotube array assembly and a preparation method thereof, a conductive agent, a pole piece and a battery, the sheet-shaped catalyst comprises a carrier, at least part of the surface of the carrier is provided with metal particles formed by a Q element, the surface of the carrier sequentially comprises a central region and an edge region, the load capacity of the Q element in the central area is greater than that of the Q element in the edge area. Therefore, in the process of preparing the carbon nanotube array assembly, the metal particles formed in the center area of the flaky catalyst are large in particle size and low in surface density and can catalyze the growth of multi-walled carbon nanotubes, and the metal particles formed in the edge area are small in particle size and high in surface density and can catalyze the growth of less / single-walled carbon nanotubes. The multi-walled carbon nanotubes can guide efficient growth of few / single-walled carbon nanotubes, and then the carbon nanotube array assembly is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and specifically, to a sheet catalyst and a preparation method thereof, a carbon nanotube array assembly and a preparation method thereof, a conductive agent, a pole piece, and a battery. Background Art

[0002] As a new type of material, carbon nanotubes have attracted much attention due to their broad application prospects in the fields of composite material reinforcement, electrochemical energy storage, and electronic devices. Among them, few-walled and single-walled carbon nanotubes have small diameters and high aspect ratios, and have superb mechanical properties, excellent electrical conductivity, excellent thermal properties, stable chemical properties, etc., and fully demonstrate excellent properties in the fields of electrochemical energy storage. And as the length of few / single-walled carbon nanotubes increases, they can construct excellent long-range conductive networks in the negative electrode materials of lithium-ion batteries, showing more excellent conductive properties. In particular, when few / single-walled carbon nanotubes grow in an array form, they have the advantages of high yield, consistent length, and easy dispersion. However, it is difficult to break through the length of batch-prepared few / single-walled carbon nanotube arrays, which greatly limits their practical applications.

[0003] Multi-walled carbon nanotubes are hard and can grow in long arrays up to hundreds of microns in length. In contrast, few-walled / single-walled carbon nanotubes are soft and their growth is easily hindered by the surrounding catalyst sheets, so their length is often difficult to match that of multi-walled carbon nanotubes.

[0004] In the process of preparing few / single-walled carbon nanotubes, by dispersing and spreading the catalyst on the container, sufficient space can be provided for the growth of few / single-walled carbon nanotubes, but the output of few / single-walled carbon nanotubes is limited by the amount of catalyst input. How to increase the growth length of few / single-walled carbon nanotubes while ensuring the output is a difficult problem to solve. Summary of the invention

[0005] The present application aims to solve one of the technical problems in the related art at least to some extent.

[0006] The first aspect of the present application provides a sheet catalyst, the sheet catalyst includes a carrier, at least part of the surface of the carrier has metal particles formed by Q element, the carrier includes an oxide containing M element, the Q element includes at least one of Fe, Co, Ni, Cu, Mo, W, and the M element includes at least one of Mg, Zn, Ca, Mn, Cr, Al, and Ru; the surface of the carrier includes a central area and an edge area from the center of the carrier to the edge of the carrier, and the load of the Q element in the central area is greater than the load of the Q element in the edge area. Thus, in the process of preparing a carbon nanotube array assembly, the load of the Q element in the central area is large, and a small number of Q metal particles with a large average particle size can be formed to catalyze the growth of multi-walled carbon nanotubes, and the load of the Q element in the edge area is small, and a large number of Q metal particles with a small average particle size can be formed to catalyze the growth of few / single-walled carbon nanotubes, and the multi-walled carbon nanotubes can play a role of pillaring, guiding the efficient growth of few / single-walled carbon nanotubes, thereby obtaining a carbon nanotube array assembly with a length of up to hundreds of microns.

[0007] According to some embodiments of the present application, the surface density of the metal particles in the central region is less than the surface density of the metal particles in the edge region, and the surface density of the metal particles in the central region is 10 12 pcs / m 2 -10 15 pcs / m 2 The surface density of the metal particles in the edge region is 10 14 pcs / m 2 -10 16 pcs / m 2 Thus, carbon nanotubes with different wall numbers are catalytically grown to obtain a carbon nanotube array assembly.

[0008] According to some embodiments of the present application, the average particle size of the metal particles in the central region is greater than the average particle size of the metal particles in the edge region. The average particle size of the metal particles in the central region is 7nm-50nm, and the average particle size of the metal particles in the edge region is 1nm-10nm.

[0009] The second aspect of the present application provides a method for preparing the sheet catalyst provided in the first aspect of the present application, the method comprising: mixing a salt solution containing M element, a precipitant, and a salt solution containing Q element to form a mixed solution, obtaining a precursor by coprecipitation, the coprecipitation comprising a first stage and a second stage carried out in sequence, the first stage being 0h-6h from the start of the coprecipitation, the mass of the Q element added in the first stage being greater than the mass of the Q element added in the second stage; calcining and reducing the precursor to obtain the sheet catalyst. Thus, the method is simple in process, and in the process of reducing the precursor, the Q element in the central region is easier to aggregate and grow than the Q element in the edge region, and a sheet catalyst with a small number of metal particles in the central region and a large average particle size, a large number of metal particles in the edge region and a small average particle size can be obtained, which is then used to prepare a carbon nanotube array assembly, thereby constructing a conductive network with excellent performance in the pole piece.

[0010] According to some embodiments of the present application, the molar ratio of the Q element to the M element in the salt solution containing the Q element added in the first stage is (0.05-0.5): 1. Therefore, the content of the Q element added in the first stage is relatively large, and it can gradually nucleate and grow in the central area of ​​the carrier to form crystals with a relatively high Q element loading.

[0011] According to some embodiments of the present application, the molar ratio of the Q element to the M element in the salt solution containing the Q element added in the second stage is (0.005-0.05): 1. Therefore, the content of the Q element added in the second stage is relatively small, and crystals with relatively small Q element loading can be formed in the edge area of ​​the carrier.

[0012] According to some embodiments of the present application, the pH of the mixed solution during the co-precipitation process is 6-11.

[0013] According to some embodiments of the present application, at least one of the following conditions is met: the calcination atmosphere is an inert gas or air; the calcination temperature is 400°C-900°C; the calcination heating rate is 1°C / min-20°C / min.

[0014] According to some embodiments of the present application, the reduction process includes: pre-treating the calcined precursor with a pre-treatment gas, wherein the pre-treatment satisfies at least one of the following conditions: the pre-treatment gas includes at least one of hydrogen, carbon monoxide, and methane; the pre-treatment temperature is 400-900° C.; and the pre-treatment time is 1 min-60 min. Thus, metal nanoparticles are formed on the surface of the carrier through the reduction process.

[0015] The third aspect of the present application provides a method for preparing a carbon nanotube array assembly, the method comprising: mixing the sheet catalyst provided by the first aspect of the present application or the sheet catalyst prepared by the method provided by the second aspect of the present application with a carbon source gas for reaction, the reaction temperature being 500°C-900°C, so as to obtain an array assembly containing multi-walled carbon nanotubes, few-walled carbon nanotubes, and single-walled carbon nanotubes at the same time. Thus, the multi-walled carbon nanotubes guide the efficient catalytic growth of the few / single-walled carbon nanotube array, increase the growth length of the few / single-walled carbon nanotubes, and obtain a carbon nanotube array assembly with significant orientation, the length of which can reach hundreds of microns, and carbon nanotubes of different diameters work together to build a conductive network with excellent performance on the pole piece.

[0016] The fourth aspect of the present application provides a carbon nanotube array assembly, which is prepared by the method provided in the third aspect of the present application, and the carbon nanotube array assembly satisfies at least one of the following conditions: the length of the carbon nanotube array assembly is 20 μm-200 μm; the diameter of the carbon nanotube array is 0.3 μm-8 μm; the specific surface area of ​​the carbon nanotube array is 300 m 2 / g-900m 2 / g. Therefore, when the carbon nanotube array assembly is used as a conductive agent on the negative electrode sheet, it can serve as a supporting skeleton to limit the volume expansion of the silicon-based negative electrode. The single-walled / few-walled carbon nanotubes have good flexibility to wrap around the silicon-based material to reduce the contact resistance. The long carbon nanotubes with different wall numbers form a conductive network, which can improve the conductivity and stability of the negative electrode active material of the ion battery.

[0017] The fifth aspect of the present application provides a conductive agent, including the carbon nanotube array assembly provided by the fourth aspect of the present application.

[0018] The sixth aspect of the present application provides a pole piece, comprising the conductive agent provided in the fifth aspect of the present application.

[0019] The seventh aspect of the present application provides a battery, comprising the electrode provided in the sixth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 A transmission electron microscope photograph showing the distribution of metal particles after pretreatment of the catalyst prepared in the example of the present application is shown.

[0021] Figure 2 A schematic flow chart of a method for preparing a sheet catalyst according to an embodiment of the present application is shown.

[0022] Figure 3This is a typical transmission electron microscope photograph of multi-walled carbon nanotubes grown inside the catalyst layer prepared in Example 1.

[0023] Figure 4 This is a typical transmission electron microscope photograph of a few / single carbon nanotubes grown on the periphery of the catalyst layer prepared in Example 1.

[0024] Figure 5 This is a typical low-magnification scanning electron microscope photograph of the long array carbon nanotubes prepared in Example 3.

[0025] Reference numerals: 1 carrier; 11 central region; 12 edge region; 21 multi-walled carbon nanotube; 22 few-walled carbon nanotube; 23 single-walled carbon nanotube. DETAILED DESCRIPTION

[0026] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0027] There are several methods to increase the length of short / single-walled carbon nanotubes. One is to disperse the catalyst on a secondary carrier, such as a stainless steel mesh, silicon wafer, quartz plate, etc., to provide sufficient space and a relatively stable growth environment for the growth of array carbon nanotubes. However, this method can only disperse a limited amount of catalyst, resulting in limited production of short / single-walled carbon nanotubes. Another method is to increase the surface density of metal particles on the catalyst layer so that the short / single-walled carbon nanotubes can spontaneously self-assemble into a double helix structure, thereby having greater support and improving growth stability to a certain extent. However, this method is only implemented in a small-scale horizontal tube furnace, and it is difficult to be widely used in large-scale reactors of different types, and cannot be mass-produced.

[0028] In a first aspect, the present application provides a sheet catalyst, which includes a carrier, at least part of the surface of the carrier has metal particles formed by Q element, the carrier includes an oxide containing M element, the Q element includes at least one of Fe, Co, Ni, Cu, Mo, W, and the M element includes at least one of Mg, Zn, Ca, Mn, Cr, Al, and Ru; the surface of the carrier includes a central area and an edge area from the center of the carrier to the edge of the carrier, and the loading amount of the Q element in the central area is greater than the loading amount of the Q element in the edge area.

[0029] In the present application, the radius of the catalyst layer is r, the central area of ​​the carrier surface refers to the range of 0-0.6r of the radius of the catalyst layer; the edge area refers to the range of 0.3rr of the radius of the catalyst layer.

[0030] For example, the central region may be in the range of 0-0.3r of the catalyst layer radius, and the edge region may be in the range of 0.3rr of the catalyst layer. When the central region is in the range of 0-0.6r of the catalyst layer, the edge region may be in the range of 0.6rr of the catalyst layer.

[0031] It should be noted that the metal particles in the edge region may be distributed only in a position close to the central region, or the metal particles may be distributed in the entire edge region.

[0032] Specifically, the sizes of the central region and the edge region can be designed according to the carbon nanotube array assembly to be prepared. For example, when preparing a carbon nanotube array assembly with a higher multi-walled carbon nanotube content and a lower low / single-walled carbon nanotube content, the central region with a higher Q element loading can be made larger, and the edge region with a lower Q element loading can be made smaller; when preparing a carbon nanotube array assembly with a lower multi-walled carbon nanotube content and a higher low / single-walled carbon nanotube content, the central region with a higher Q element loading can be made smaller, and the edge region with a lower Q element loading can be made larger.

[0033] For example, refer to Figure 1 The central area 11 and the edge area 12 of the sheet-shaped catalyst carrier 1 are shown in the figure.

[0034] In the present application, the surface density and average particle size of the metal particles in the central area and the edge area can be observed and compared by scanning electron microscopy. When calculating the surface density, it refers to the surface density of the area where the metal particles exist.

[0035] Therefore, in the process of preparing the carbon nanotube array assembly, the loading amount of the Q element in the central area is relatively large, and a smaller number of Q metal particles with a larger average particle size can be formed to catalyze the growth of multi-walled carbon nanotubes. The loading amount of the Q element in the edge area is relatively small, and a larger number of Q metal particles with a smaller average particle size can be formed to catalyze the growth of few / single-walled carbon nanotubes. The multi-walled carbon nanotubes can play a pillar role, guiding the efficient growth of few / single-walled carbon nanotubes, thereby obtaining a carbon nanotube array assembly with a length of up to hundreds of microns.

[0036] As an example, the carrier can be prepared from flaky magnesium hydroxide or layered double metal hydroxide.

[0037] According to some embodiments of the present application, the surface density of the metal particles in the central region is less than the surface density of the metal particles in the edge region, and the surface density of the metal particles in the central region is 10 12pcs / m 2 -10 15 pcs / m 2 The surface density of the metal particles in the edge region is 10 14 pcs / m 2 -10 16 pcs / m 2 Thus, carbon nanotubes with different wall numbers are catalytically grown to obtain a carbon nanotube array assembly.

[0038] As an example, the surface density of the metal particles in the central region may be 10 12 pcs / m 2 , 10 13 pcs / m 2 , 10 14 pcs / m 2 , 10 15 pcs / m 2 The above-mentioned arbitrary numerical ranges may also be used.

[0039] As an example, the surface density of the metal particles in the edge region may be 10 14 pcs / m 2 , 10 15 pcs / m 2 , 10 16 pcs / m 2 The above-mentioned arbitrary numerical ranges may also be used.

[0040] According to some embodiments of the present application, the average particle size of the metal particles in the central region is greater than the average particle size of the metal particles in the edge region. The average particle size of the metal particles in the central region is 7nm-50nm, and the average particle size of the metal particles in the edge region is 1nm-10nm.

[0041] As an example, the average particle size of the metal particles in the central region may be 7 nm, 20 nm, 30 nm, 40 nm, 50 nm, etc., or may be a range consisting of any of the above values.

[0042] As an example, the average particle size of the metal particles in the edge region may be 1 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 10 nm, etc., or may be a range consisting of any of the above values.

[0043] As a result, the number of metal particles in the central area of ​​the catalyst is relatively small and the average particle size is relatively large, while the number of metal particles in the edge area is relatively large and the average particle size is relatively small. In the process of preparing carbon nanotubes, the metal particles in the central area can catalyze the growth of multi-walled carbon nanotubes in an array structure, play a pillar role, and expand the surrounding sheet catalysts. The macroscopic volume of the catalyst bed is greatly expanded. The metal particles in the edge area can catalyze the growth of few / single-walled carbon nanotubes. The few / single-walled carbon nanotubes cling to the multi-walled carbon nanotubes and also grow in an array structure, which is beneficial to increase the growth length of the few / single-walled carbon nanotubes. The obtained carbon nanotube array assembly has significant orientation and can reach hundreds of microns in length. Carbon nanotubes of different diameters work synergistically to build a conductive network with excellent performance on the electrode.

[0044] The second aspect of the present application provides a method for preparing the sheet catalyst provided in the first aspect of the present application, the method comprising: mixing a salt solution containing the M element, a precipitant, and a salt solution containing the Q element to form a mixed solution, obtaining a precursor by coprecipitation, the coprecipitation comprising a first stage and a second stage carried out in sequence, the first stage being 0h-6h at the beginning of the coprecipitation, the mass of the Q element added in the first stage being greater than the mass of the Q element added in the second stage; calcining and reducing the precursor to obtain the sheet catalyst. That is to say, in the first stage at the beginning of the coprecipitation, a high content of active metal Q is added, and in the subsequent stages of the coprecipitation, a low content of active metal Q is added, thereby obtaining a sheet catalyst with a relatively small number of metal particles in the central region and a large average particle size, and a relatively large number of metal particles in the edge region and a small average particle size, which is then used to prepare a carbon nanotube array assembly, thereby constructing a conductive network with excellent performance in the pole piece.

[0045] The method provided by this application is described in detail below. Figure 2 , the method comprising: S10: Mix a salt solution containing the M element, a precipitant, and a salt solution containing the Q element to form a mixed solution, and obtain a precursor by coprecipitation. According to some embodiments of the present application, a salt solution containing the M element, a precipitant, and a salt solution containing the Q element are mixed to form a mixed solution, and a precursor is obtained by co-precipitation. The co-precipitation includes a first stage and a second stage which are performed sequentially. The first stage is 0h-6h from the start of the co-precipitation, and the mass of the Q element added in the first stage is greater than the mass of the Q element added in the second stage.

[0046] According to some embodiments of the present application, the mixing method of the salt solution containing the M element, the salt solution containing the Q element and the precipitant is not limited. The salt solution containing the M element and the salt solution containing the Q element may be first added to the precipitant solution to form a mixed solution, and then the mixed solution is added to the reactor; or the salt solution containing the M element, the salt solution containing the Q element and the precipitant solution are simultaneously added dropwise to the reactor; or the salt solution containing the M element, the salt solution containing the Q element and the precipitant solution are directly added to the reactor as a whole.

[0047] According to some embodiments of the present application, the method of adding the precipitant solution is not particularly limited. It can be that the salt solution containing the M element, the salt solution containing the Q element and half the volume of the precipitant solution are first mixed to form a mixed solution, which is then added to the reactor. When the salt solution containing the Q element is added in the second stage of co-precipitation, the salt solution containing the Q element is then mixed with the other half volume of the precipitant solution and added to the reactor.

[0048] According to some embodiments of the present application, the salt solution containing element M includes at least one of sulfate containing M, nitrate containing M, chloride containing M, and acetate containing M.

[0049] According to some embodiments of the present application, the precipitant includes at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate, ammonium bicarbonate, urea, and ammonia water.

[0050] According to some embodiments of the present application, the salt solution containing Q includes at least one of a sulfate containing Q, a nitrate containing Q, a chloride containing Q, and an acetate containing Q.

[0051] According to some embodiments of the present application, the first stage is 0h-6h from the start of the coprecipitation, for example, it can be 0.5h, 1h, 2h, 3h, 4h, 5h, etc., or it can be a range of any of the above numerical values. For example, a high content of active metal is added 0-3h after the start of the reaction to carry out the first stage of coprecipitation, and then a low content of active metal is added 3h later to carry out the second stage of coprecipitation until the reaction is completed.

[0052] According to some embodiments of the present application, the molar ratio of the Q element to the M element in the salt solution containing the Q element added in the first stage is (0.05-0.5):1, for example, it can be 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, etc., or it can be a range consisting of any of the above numerical values.

[0053] According to some embodiments of the present application, the molar ratio of the Q element to the M element in the salt solution containing the Q element added in the second stage is (0.005-0.05):1, for example, it can be 0.005:1, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, etc., or can be a range consisting of any of the above numerical values.

[0054] Therefore, a high content of active metal Q is added at the beginning of the co-precipitation stage, and a low content of active metal Q is added in the subsequent stage of the co-precipitation, so as to obtain a sheet catalyst with relatively fewer metal nanoparticles and a larger average particle size in the central region and relatively more metal nanoparticles and a smaller average particle size in the edge region. In the process of preparing carbon nanotubes, the metal particles in the central region can catalyze the growth of multi-walled carbon nanotubes in an array structure and play a role of pillar support. The metal particles in the edge region can catalyze the growth of few / single-walled carbon nanotubes. The few / single-walled carbon nanotubes cling to the multi-walled carbon nanotubes and also grow in an array structure, which is beneficial to increase the growth length of the few / single-walled carbon nanotubes. The obtained carbon nanotube array assembly has significant orientation and can reach hundreds of microns in length. Carbon nanotubes of different diameters work synergistically to build a conductive network with excellent performance on the electrode.

[0055] According to some embodiments of the present application, the pH of the mixed solution during the co-precipitation process is 6-11, for example, it can be 6, 7, 8, 9, 10, 11, etc., or it can be a range consisting of any of the above values.

[0056] According to some embodiments of the present application, the co-precipitation further includes the steps of standing and aging, and then the product is filtered, washed to neutrality, dried, ground and crushed to obtain a flaky catalyst.

[0057] S20: calcining the precursor According to some embodiments of the present application, the calcination atmosphere may be an inert gas or air.

[0058] According to some embodiments of the present application, the heating rate of the calcination can be 1°C / min-20°C / min, for example, it can be 1°C / min, 5°C / min, 10°C / min, 15°C / min, 20°C / min, etc., or it can be a range composed of any of the above numerical values.

[0059] According to some embodiments of the present application, the calcination temperature may be 400°C-900°C, for example, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, etc., or may be a range consisting of any of the above numerical values.

[0060] S30: Reduction of the calcined precursor According to some embodiments of the present application, the calcined precursor is placed in a reactor, and a pretreatment gas is introduced to reduce the precursor.

[0061] According to some embodiments of the present application, the pretreatment gas includes at least one of hydrogen, carbon monoxide, and methane.

[0062] According to some embodiments of the present application, the pretreatment temperature is 400°C-900°C, for example, it can be 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, etc., or it can be a range consisting of any of the above numerical values.

[0063] According to some embodiments of the present application, the pretreatment time is 1 min-60 min, for example, it can be 1 min, 10 min, 30 min, 45 min, 60 min, etc., or it can be a range consisting of any of the above numerical values.

[0064] Thus, Q metal nanoparticles are formed on the surface of the support through a reduction process.

[0065] The third aspect of the present application provides a method for preparing a carbon nanotube array assembly, the method comprising: mixing the sheet catalyst provided by the first aspect of the present application or the catalyst prepared by the method provided by the second aspect of the present application with a carbon source gas for reaction, the reaction temperature being 500°C-900°C, so as to obtain an array assembly containing multi-walled carbon nanotubes, few-walled carbon nanotubes, and single-walled carbon nanotubes at the same time. Thus, a sheet catalyst having a small number of metal nanoparticles in the central region and a large average particle size, and a large number of metal nanoparticles in the edge region and a small average particle size is used. In the process of preparing carbon nanotubes, the metal particles in the central region can catalyze the growth of multi-walled carbon nanotubes in an array structure, playing a role of pillar support, and the metal particles in the edge region can catalyze the growth of few / single-walled carbon nanotubes, and the few / single-walled carbon nanotubes are attached to the multi-walled carbon nanotubes and also grow in an array structure, which is conducive to increasing the growth length of the few / single-walled carbon nanotubes. The obtained carbon nanotube array assembly has significant orientation, and the length can reach hundreds of microns. Carbon nanotubes of different diameters work together to build a conductive network with excellent performance on the pole piece.

[0066] According to some embodiments of the present application, a sheet catalyst is placed in a reactor, and a mixture of carbon source gas, hydrogen, and carrier gas is introduced into the reactor. The reaction temperature is 500°C-900°C, and the volume ratio of hydrogen, carbon source gas, and carrier gas in the mixture is (0-10):1:(0.1-10).

[0067] As an example, the reaction temperature may be 500° C., 600° C., 700° C., 800° C., 900° C., etc., or may be in a range consisting of any of the above values.

[0068] According to some embodiments of the present application, the reactor includes at least one of a fixed bed, a fluidized bed, a moving bed, and a rotating drum.

[0069] According to some embodiments of the present application, the carbon source gas includes at least one of methane, methanol, ethylene, ethane, ethanol, propylene, propane, carbon monoxide, natural gas, liquefied petroleum gas, cyclohexane, n-hexane, benzene or toluene.

[0070] According to some embodiments of the present application, the volume space velocity of the mixed gas is 10min -1 -10 7 min -1 .

[0071] The fourth aspect of the present application provides a carbon nanotube array assembly, which is prepared by the method provided by the third aspect of the present application.

[0072] According to some embodiments of the present application, the length of the carbon nanotube array assembly is 20 μm-200 μm, for example, 20 μm, 50 μm, 80 μm, 110 μm, 140 μm, 170 μm, 200 μm, etc., or a range consisting of any of the above values.

[0073] According to some embodiments of the present application, the diameter of the carbon nanotube array is 0.3 μm-8 μm, for example, 0.3 μm, 1 μm, 3 μm, 5 μm, 7 μm, 8 μm, etc., or a range consisting of any of the above values.

[0074] According to some embodiments of the present application, the specific surface area of ​​the carbon nanotube array is 300 m 2 / g-900m 2 / g. For example, it can be 300m 2 / g, 400m 2 / g、500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g, etc., or may be within the range consisting of any of the above values.

[0075] Therefore, when the carbon nanotube array assembly is used as a conductive agent on the negative electrode plate, it can serve as a supporting skeleton to limit the volume expansion of the silicon-based negative electrode. The single / few-walled carbon nanotubes have good flexibility to wrap around the silicon-based material to reduce the contact resistance. The long carbon nanotubes with different wall numbers form a conductive network, which can improve the conductivity and stability of the negative electrode active material of the ion battery.

[0076] The fifth aspect of the present application provides a conductive agent, including the carbon nanotube array assembly provided by the fourth aspect of the present application.

[0077] The carbon nanotube array assembly proposed in the present application includes multi-walled, few-walled, and single-walled long array carbon nanotubes. When the carbon nanotube assembly is used as a conductive agent on the negative electrode plate, it can serve as a supporting skeleton to limit the volume expansion of the silicon-based negative electrode. The single / few-walled carbon nanotubes have good flexibility to wrap around the silicon-based material to reduce the contact resistance. The long carbon nanotubes with different wall numbers constitute a conductive network, which can improve the conductivity and stability of the negative electrode active material of the ion battery.

[0078] In the present application, multi-walled carbon nanotubes refer to carbon nanotubes with 5-20 walls, and few-walled carbon nanotubes refer to carbon nanotubes with 2-4 walls.

[0079] The sixth aspect of the present application provides a pole piece, comprising the conductive agent provided in the fifth aspect of the present application.

[0080] The seventh aspect of the present application provides a battery, comprising the electrode provided in the sixth aspect of the present application.

[0081] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0082] Example 1 Preparation of carbon nanotube arrays in a fixed bed using MgAl layered double hydroxide loaded with Fe: (1) Dissolve 0.2 mol magnesium sulfate, 0.05 mol aluminum sulfate and 0.1 mol iron sulfate in water and stir well to form solution A; Dissolve 1.5 mol of sodium bicarbonate in water and stir to form solution B; Dissolve 0.2 mol magnesium sulfate, 0.05 mol aluminum sulfate and 0.01 mol ferric sulfate in water and stir well to form solution C.

[0083] (2) Solution A was added dropwise to solution B, the temperature was set to 80 °C, the stirring speed was 300 rpm, and the reaction was continued for 2 h. Then solution C was added dropwise to the mixed solution of A and B, the end point pH was 8-10, the reaction was stirred for 6 h under the same conditions, and the mixture was allowed to stand for 12 h. After the reaction was completed, the product was filtered and washed to neutrality, the solid was dried at 80 °C in a forced air drying oven, and ground to obtain a flaky catalyst. The transmission electron microscope photo of the catalyst is shown in Figure 1 .

[0084] The steps for synthesizing carbon nanotube arrays using the flake catalyst are as follows: (1) 0.5 g of the catalyst flakes were placed in a fixed bed reactor, 0.5 L / min of nitrogen was introduced, the temperature was raised to 650 °C, and 0.2 L / min of hydrogen was introduced for pretreatment for 10 min; (2) 0.5 L / min ethylene was introduced at 650 °C for 30 min to prepare carbon nanotube arrays. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and the black fluffy product was collected.

[0085] After catalyst reduction, the Fe particles in the center of the sheet are larger (20nm-50nm) and the surface density is 3×10 14 m -2 The loading amount of Fe element is 27wt%, the particle size of Fe particles in the edge area is small (2nm-7nm), and the surface density is 1×10 15 m -2 The loading amount of Fe element is 3.5wt%. The carbon nanotubes grown in the center area of ​​the layered catalyst are multi-walled carbon nanotubes, and the edge area is few / single-walled carbon nanotubes, all of which grow in a long array structure. The length of the carbon nanotube array assembly is 50μm-100μm, the diameter is 1.2μm, and the specific surface area is 569m 2 / g, reference Figure 3 It can be seen that the prepared carbon nanotube array assembly contains reference Figure 4 It can be seen that the prepared carbon nanotube array assembly contains few / single-walled carbon nanotubes.

[0086] The carbon nanotube array assembly was subjected to liquid phase impurity removal and dispersed in water to obtain a carbon nanotube slurry, which contained multi-walled carbon nanotubes and few / single-walled carbon nanotubes. The carbon nanotube slurry was mixed with silicon-carbon negative electrode material, binder carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) to obtain an electrode slurry. The mass ratio of silicon-carbon negative electrode material: carbon nanotube array assembly: CMC: SBR in the electrode slurry was 93:0.5:1:2. The electrode slurry was coated on an insulating polyethylene terephthalate (PET film) and dried to form an active material layer. The thickness of the active material layer was 30μm. The resistivity of the electrode sheet was tested by a four-probe resistivity meter and was 1.33Ω·cm. The resistivity was low, indicating that the carbon nanotube array assembly can improve the conductivity of the electrode sheet.

[0087] Example 2 Preparation of carbon nanotube arrays in a fixed bed using MgAl layered double hydroxide loaded with FeCo: (1) Dissolve 0.2 mol magnesium sulfate, 0.05 mol aluminum nitrate and 0.05 mol ferric nitrate in water and stir well to form solution A; Dissolve 1.46 mol of sodium bicarbonate in water and stir to form solution B; Dissolve 0.2 mol magnesium sulfate, 0.05 mol aluminum nitrate and 0.01 mol cobalt nitrate in water and stir well to form solution C.

[0088] (2) Solution A and half the volume of solution B were added dropwise at the same time, and the addition rate was set to 5 mL / min. The pH was always kept at 8-10, the temperature was 80 °C, the stirring speed was 300 rpm, and the reaction was carried out for 2 h. Then, solution C and the remaining half the volume of solution B were added dropwise to the above mixed solution at the same time, and the reaction was stirred for 6 h under the same conditions, and then allowed to stand for 12 h. After the reaction was completed, the product was filtered, washed until neutral, and the solid was dried at 80 °C in a forced air drying oven, and ground and crushed to obtain a flake catalyst.

[0089] The steps for synthesizing carbon nanotube arrays using the flake catalyst are as follows: (1) 0.5 g of the catalyst flakes were placed in a fixed bed reactor, 0.5 L / min of nitrogen was introduced, the temperature was raised to 750 °C, and 0.2 L / min of hydrogen was introduced for pretreatment for 10 min; (2) 0.5 L / min ethylene was introduced at 750 °C for 60 min to prepare carbon nanotube arrays. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and the black fluffy product was collected.

[0090] After catalyst reduction, the Fe particles in the center of the sheet are larger (10nm-30nm) and the surface density is 2×10 14 pcs / m 2 The loading amount of Fe element is 16wt%, the particle size of Co particles in the edge area is small (2nm-4nm), and the surface density is 5×10 15 pcs / m 2 The loading amount of Co element is 3.7wt%. The carbon nanotubes grown in the center area of ​​the sheet are multi-walled carbon nanotubes, and the edge area is few / single-walled carbon nanotubes, all of which grow in a long array structure. The length of the carbon nanotube array assembly is 50μm-200μm, the diameter is 1.2μm, and the specific surface area is 661m 2 / g.

[0091] The preparation method of the electrode sheet is the same as that of Example 1. The resistivity of the electrode sheet is 1.06 Ω·cm as measured by a four-probe resistivity meter. The resistivity is relatively low, indicating that the carbon nanotube array assembly can improve the conductivity of the electrode sheet.

[0092] Example 3 Preparation of carbon nanotube arrays in a fixed bed using MgAl layered double hydroxide loaded with NiCo: (1) Dissolve 0.1 mol magnesium nitrate, 0.05 mol aluminum nitrate, and 0.08 mol nickel nitrate in water and stir to form solution A. Dissolve 3 mol urea in water and stir well to form solution B; Dissolve 0.1 mol magnesium sulfate, 0.05 mol aluminum nitrate and 0.01 mol cobalt nitrate in water and stir well to form solution C.

[0093] (2) Solution A and solution B were directly mixed in one pot, the temperature was set to 95 °C, the stirring speed was 200 rpm, and the reaction was carried out for 1 h. Then solution C was added dropwise to the mixed solution of A and B, the end point pH was 7-11, the reaction was stirred for 10 h under the same conditions, and the reaction was allowed to stand for 12 h. After the reaction was completed, the product was filtered and washed to neutrality, the solid was dried at 80 °C in a forced air drying oven, and ground to obtain a flaky catalyst.

[0094] The steps for synthesizing carbon nanotube arrays using the flake catalyst are as follows: (1) 0.5 g of the catalyst flakes were placed in a fixed bed reactor, 0.5 L / min of nitrogen was introduced, the temperature was raised to 700 °C, and 0.2 L / min of methane was introduced for pretreatment for 10 min; (2) 0.5 L / min propylene was introduced at 700 °C for 45 min to prepare carbon nanotube arrays. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and the black fluffy product was collected.

[0095] After catalyst reduction, the Ni particles in the center of the sheet are larger (10nm-35nm) and the surface density is 3.5×10 14 pcs / m 2 The loading amount of Ni element is 48wt%, the particle size of Co particles in the edge area is small (2nm-4nm), and the surface density is 5.5×10 15 pcs / m 2 The loading amount of Co element is 6.2wt%. The carbon nanotubes grown in the center area of ​​the sheet are multi-walled, and the edge area is few / single-walled. They all grow in a long array structure. The length of the carbon nanotube array assembly is 20μm-100μm, the diameter is 1.6μm, and the specific surface area is 605m 2 / g, the structure of carbon nanotube array assembly is shown in Figure 5 .

[0096] The preparation method of the electrode sheet is the same as that of Example 1. The resistivity of the electrode sheet is 1.17 Ω·cm as measured by a four-probe resistivity meter. The resistivity is relatively low, indicating that the carbon nanotube array assembly can improve the conductivity of the electrode sheet.

[0097] Example 4 Preparation of carbon nanotube arrays in a fluidized bed using flake magnesium hydroxide loaded with Cu: (1) Dissolve 0.2 mol magnesium nitrate in water to form solution A; Dissolve 0.65 mol of sodium hydroxide in water and stir well to form solution B; Dissolve 0.1 mol copper nitrate in water and stir to form solution C; Dissolve 0.01 mol copper nitrate in water and stir well to form solution D.

[0098] (2) Mix half the volume of solution A with solution C, add dropwise to solution B, set the temperature to 100 °C, stir at 150 rpm, and react for 0.5 h. Then mix the remaining volume of solution A with solution D, add dropwise to solution B, the end point pH is 8-11, stir for 3 h under the same conditions, and let stand for 12 h. After the reaction is completed, filter the product, wash until neutral, take the solid and dry it at 80 °C in a forced air drying oven, grind and crush to obtain a flake catalyst.

[0099] The steps for synthesizing carbon nanotube arrays using the flake catalyst are as follows: (1) 0.5 g of the catalyst flakes were placed in a fixed bed reactor, 0.5 L / min of nitrogen was introduced, the temperature was raised to 800 °C, and 0.2 L / min of carbon monoxide was introduced for pretreatment for 10 min; (2) 0.5 L / min natural gas was introduced at 800 °C for 120 min to prepare carbon nanotube arrays. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and the black fluffy product was collected.

[0100] After catalyst reduction, the Cu particles in the center of the sheet are larger (10nm-40nm) and the surface density is 3×10 14 pcs / m 2 The Cu loading is 39wt%, the Cu particles in the edge area are small (2nm-7nm), and the surface density is 4×10 15 pcs / m 2 The loading amount of Cu element is 4.8wt%. The carbon nanotubes grown in the center area of ​​the sheet are multi-walled, and the edge area is few / single-walled. They all grow in a long array structure. The length of the carbon nanotube array assembly is 20μm-100μm, the diameter is 0.8μm, and the specific surface area is 573m 2 / g.

[0101] The preparation method of the electrode sheet is the same as that of Example 1. The resistivity of the electrode sheet is 1.25 Ω·cm as measured by a four-probe resistivity meter. The resistivity is relatively low, indicating that the carbon nanotube array assembly can improve the conductivity of the electrode sheet.

[0102] Example 5 Carbon nanotube arrays were prepared in a fluidized bed using flaky magnesium hydroxide loaded with FeNi: (1) Dissolve 0.2 mol magnesium nitrate in water to form solution A; Dissolve 0.9 mol of ammonia in water and stir to form solution B; Dissolve 0.1 mol of ferric nitrate in water and stir well to form solution C; Dissolve 0.02 mol nickel nitrate in water and stir well to form solution D.

[0103] (2) Add half the volume of solution A and solution C to solution B dropwise at the same time, set the temperature to 105 °C, stir at 200 rpm, and react for 2 h. Then add the remaining volume of solution A and solution D to solution B dropwise at the same time, with the end point pH being 7-10, stir for 4 h under the same conditions, and let stand for 24 h. After the reaction is completed, filter the product, wash until neutral, take the solid and dry it at 80 °C in a forced air drying oven, grind and crush to obtain a flake catalyst.

[0104] The steps for synthesizing carbon nanotube arrays using the flake catalyst are as follows: (1) 0.5 g of the catalyst flakes were placed in a fixed bed reactor, 0.5 L / min of nitrogen was introduced, the temperature was raised to 800 °C, and 0.2 L / min of hydrogen was introduced for pretreatment for 10 min; (2) 0.5 L / min methane was introduced at 850 °C for 120 min to prepare carbon nanotube arrays. After the reaction was completed, the temperature was lowered to room temperature under inert gas protection, and the black fluffy product was collected.

[0105] After catalyst reduction, the Fe particles in the center of the sheet are larger (10nm-40nm) and the surface density is 3×10 14 pcs / m 2 The loading amount of Fe element is 34wt%, the particle size of Ni particles in the edge area is small (2nm-7nm), and the surface density is 5×10 15 pcs / m 2 The loading amount of Ni element is 7.9wt%. The carbon nanotubes grown in the center area of ​​the sheet are multi-walled, and the edge area is few / single-walled. They all grow in a long array structure. The length of the carbon nanotube array assembly is 20μm-50μm, the diameter is 1.0μm, and the specific surface area is 592m2 / g.

[0106] The preparation method of the electrode sheet is the same as that of Example 1. The resistivity of the electrode sheet is 1.27 Ω·cm as measured by a four-probe resistivity meter. The resistivity is relatively low, indicating that the carbon nanotube array assembly can improve the conductivity of the electrode sheet.

[0107] Comparative Example 1 On the basis of Example 1, only the content of active metal introduced in the initial stage and the amount of precipitant used were changed. The specific steps are as follows: Preparation of carbon nanotube arrays in a fixed bed using MgAl layered double hydroxide loaded with Fe: (1) Dissolve 0.2 mol magnesium sulfate, 0.05 mol aluminum sulfate, and 0.01 mol ferric sulfate in water and stir well to form solution A. Dissolve 1.218 mol sodium bicarbonate in water and stir well to form solution B. Dissolve 0.2 mol magnesium sulfate, 0.05 mol aluminum sulfate, and 0.01 mol ferric sulfate in water and stir well to form solution C.

[0108] (2) Solution A was added dropwise to solution B, the temperature was set to 80 °C, the stirring speed was 300 rpm, and the reaction was carried out for 2 h. Then solution C was added dropwise to the mixed solution of A and B, and the reaction was stirred for 6 h under the same conditions, and then allowed to stand for 12 h. After the reaction was completed, the product was filtered and washed to neutrality, and the solid was dried at 80 °C in a forced air drying oven, and ground to obtain a flaky catalyst.

[0109] The steps of synthesizing carbon nanotubes using the sheet catalyst are the same as those in Example 1. After the catalyst is reduced, the Fe particles distributed on the sheet layer have uniform particle size (2nm-4nm) and uniform surface density (3×10 15 pcs / m 2 The grown carbon nanotubes are all single-walled and double-walled, growing in a mesh-like interwoven structure, and failing to form an array structure. The length is 2μm-4μm, and the specific surface area is 907m 2 / g.

[0110] This indicates that when the same low content of active metal is introduced in the initial and subsequent stages of the carrier precipitation growth, the obtained active metal nanoparticles are uniformly distributed in the form of small particle sizes, and the carbon nanotubes grow in a small diameter, non-array structure, making it difficult to obtain long carbon nanotubes.

[0111] The preparation method of the electrode sheet is the same as that of Example 1. The resistivity of the electrode sheet is 2.31Ω·cm as measured by a four-probe resistivity meter. This resistivity indicates that when the carbon nanotubes grow in a small diameter, non-array, non-assembly form, the effect of improving the conductivity of the silicon-carbon negative electrode is low.

[0112] Comparative Example 2 On the basis of Example 2, only the content of active metal introduced in the subsequent stage and the amount of precipitant used are changed. The specific steps are as follows: Preparation of carbon nanotube arrays in a fixed bed using MgAl layered double hydroxide loaded with FeCo: (1) Dissolve 0.2 mol magnesium sulfate, 0.05 mol aluminum nitrate, and 0.05 mol ferric nitrate in water and stir to form solution A. Dissolve 1.55 mol sodium bicarbonate in water and stir to form solution B. Dissolve 0.2 mol magnesium sulfate, 0.05 mol aluminum nitrate, and 0.05 mol cobalt nitrate in water and stir to form solution C.

[0113] (2) Solution A was added dropwise to solution B, the temperature was set to 80 °C, the stirring speed was 300 rpm, and the reaction was carried out for 2 h. Then solution C was added dropwise to the mixed solution of A and B, and the reaction was stirred for 6 h under the same conditions, and then allowed to stand for 12 h. After the reaction was completed, the product was filtered and washed to neutrality, and the solid was dried at 80 °C in a forced air drying oven, and ground to obtain a flaky catalyst.

[0114] The steps of synthesizing carbon nanotubes using the sheet catalyst are the same as those in Example 2. After the catalyst is reduced, the Fe and Co particles distributed on the sheet are located in the central area and the edge area, respectively, with uniform particle size (10 nm-20 nm) and uniform surface density (6×10 14 pcs / m 2 The grown carbon nanotubes are all multi-walled and grow in a long array structure with a length of 100μm-200μm, a diameter of 1.2μm, and a specific surface area of ​​328m 2 / g.

[0115] This indicates that by introducing the same high content of active metal in the initial and subsequent stages of the carrier precipitation growth, the obtained active metal nanoparticles are uniformly distributed in the form of large particle sizes, the carbon nanotubes grow in a large diameter and array structure, and long carbon nanotubes are easily obtained.

[0116] The preparation method of the electrode sheet is the same as that of Example 1. The resistivity of the electrode sheet is 1.75Ω·cm when tested by a four-probe resistivity meter. This resistivity indicates that when carbon nanotubes grow in the form of large diameter, array, and non-assembly, the effect of improving the conductivity of the silicon-carbon negative electrode is limited.

[0117] Comparative Example 3 Based on Example 3, only the content of active metal introduced in the initial and subsequent stages is exchanged, and the specific steps are as follows: Preparation of carbon nanotube arrays in a fixed bed using MgAl layered double hydroxide loaded with NiCo: (1) Dissolve 0.1 mol magnesium nitrate, 0.05 mol aluminum nitrate, and 0.01 mol nickel nitrate in water and stir to form solution A. Dissolve 3 mol urea in water and stir to form solution B. Dissolve 0.1 mol magnesium sulfate, 0.05 mol aluminum nitrate, and 0.08 mol cobalt nitrate in water and stir to form solution C.

[0118] (2) Solution A and solution B were directly mixed in one pot, the temperature was set to 95 °C, the stirring speed was 200 rpm, and the reaction was carried out for 1 h. Then solution C was added dropwise to the mixed solution of A and B, stirred for 10 h under the same conditions, and allowed to stand for aging for 12 h. After the reaction was completed, the product was filtered and washed to neutrality, and the solid was dried at 80 °C in a forced air drying oven, and ground to obtain a flake catalyst.

[0119] The steps of synthesizing carbon nanotubes using the sheet catalyst are the same as those in Example 3. After the catalyst is reduced, the Ni particles in the center of the sheet are smaller in size (2nm-3nm) and have a surface density of 4×10 15 pcs / m 2 The Co particles in the edge area are larger (10nm-20nm) and the surface density is 4×10 14 pcs / m 2 The grown carbon nanotubes have few / single walls in the center, grow in a mesh-like structure, and have a length of 1μm-3μm; the edge regions have multiple walls, grow in a long array structure, have a length of 100μm-200μm, and a specific surface area of ​​406m 2 / g.

[0120] It shows that the introduction of low and high content of active metals in the initial stage and subsequent stage of the carrier precipitation growth respectively results in the distribution of active metal nanoparticles with small particle size in the center area and large particle size in the edge area. The carbon nanotubes in the center area grow with small diameter and non-array structure, which makes it difficult to grow long; the carbon nanotubes in the edge area grow with large diameter and array structure, which makes it easy to obtain long carbon nanotubes. The multi-walled carbon nanotubes in the edge area fail to form pillars for the few / single-walled carbon nanotubes in the center area, and cannot guide them to form long arrays.

[0121] The preparation method of the electrode sheet is the same as that of Example 1. The resistivity of the electrode sheet is 1.70Ω·cm when tested by a four-probe resistivity meter. This resistivity indicates that when carbon nanotubes grow in the form of large-diameter arrays and small-diameter non-array assemblies, the effect of improving the conductivity of the silicon-carbon negative electrode is limited.

[0122] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A sheet catalyst, characterized in that: A carrier is included, wherein at least a portion of the surface of the carrier has metal particles formed of Q elements, the carrier includes an oxide containing M elements, the Q element includes at least one of Fe, Co, Ni, Cu, Mo, and W, and the M element includes at least one of Mg, Zn, Ca, Mn, Cr, Al, and Ru; The surface of the carrier includes a central region and an edge region in sequence from the center of the carrier to the edge of the carrier, and the loading amount of the Q element in the central region is greater than the loading amount of the Q element in the edge region.

2. The sheet catalyst according to claim 1, characterized in that The surface density of the metal particles in the central region is less than that in the edge region. The surface density of the metal particles in the central region is 10 12 pcs / m 2 -10 15 pcs / m 2 The surface density of the metal particles in the edge region is 10 14 pcs / m 2 -10 16 pcs / m 2 .

3. The sheet catalyst according to claim 1 or 2, characterized in that: The average particle size of the metal particles in the central region is greater than the average particle size of the metal particles in the edge region. The average particle size of the metal particles in the central region is 7nm-50nm, and the average particle size of the metal particles in the edge region is 1nm-10nm.

4. A method for preparing the sheet catalyst according to any one of claims 1 to 3, characterized in that: include: A salt solution containing the M element, a precipitant, and a salt solution containing the Q element are mixed to form a mixed solution, and a precursor is obtained by coprecipitation, wherein the coprecipitation includes a first stage and a second stage performed sequentially, wherein the first stage is 0h-6h from the start of the coprecipitation, and the mass of the Q element added in the first stage is greater than the mass of the Q element added in the second stage; The precursor is calcined and reduced to obtain the sheet-like catalyst.

5. The method according to claim 4, characterized in that The molar ratio of the Q element to the M element in the salt solution containing the Q element added in the first stage is (0.05-0.5):

1.

6. The method according to claim 5, characterized in that The molar ratio of the Q element to the M element in the salt solution containing the Q element added in the second stage is (0.005-0.05):

1.

7. The method according to claim 4, characterized in that During the coprecipitation process, the pH of the mixed solution is 6-11.

8. The method according to claim 4, characterized in that At least one of the following conditions is met: (1) The calcination atmosphere is an inert gas or air; (2) The calcination temperature is 400°C-900°C; (3) The heating rate of the calcination is 1°C / min-20°C / min.

9. The method according to claim 4, characterized in that The reduction process includes: pre-treating the calcined precursor by a pre-treatment gas, wherein the pre-treatment satisfies at least one of the following conditions: (1) The pretreatment gas includes at least one of hydrogen, carbon monoxide, and methane; (2) The pretreatment temperature is 400°C-900°C; (3) The pretreatment time is 1 min to 60 min.

10. A method for preparing a carbon nanotube array assembly, characterized in that: include: The sheet catalyst described in any one of claims 1 to 3 or the sheet catalyst prepared by the method described in any one of claims 4 to 9 is mixed with a carbon source gas for reaction at a temperature of 500° C. to 900° C. to obtain an array assembly containing multi-walled carbon nanotubes, few-walled carbon nanotubes, and single-walled carbon nanotubes.

11. A carbon nanotube array assembly, characterized in that: The carbon nanotube array assembly is prepared by the method according to claim 10, wherein the carbon nanotube array assembly satisfies at least one of the following conditions: (1) The length of the carbon nanotube array assembly is 20 μm-200 μm; (2) The diameter of the carbon nanotube array is 0.3 μm-8 μm; (3) The specific surface area of ​​the carbon nanotube array is 300 m 2 / g-900m 2 / g.

12. A conductive agent, characterized in that: Comprising the carbon nanotube array assembly as claimed in claim 11.

13. A pole piece, characterized in that: Includes the conductive agent as claimed in claim 12.

14. A battery, characterized in that: Including the pole piece as claimed in claim 13.

Citation Information

Patent Citations

  • Method for preparing minor-diameter carbon nanotube array on surface of flaky material

    CN101665249A

  • Porous cobalt oxide catalyst preparation method

    CN102909022A

  • Synthesis method of lamellar structure catalyst

    CN114618544A

  • Carbon nanotube-based device and method for making the same

    US20040191158A1

  • Carbon Nanotube Device and Process for Producing the Same

    US20070231486A1